​​ Discipline, Allowances, Organizational Performance And Job Satisfaction In Four Star Hotels - Cindy Prasatya; Elsye Tandelilin; Noviaty Kresna Darmasetiawan (Eqien - Jurnal Ekonomi dan Bisnis, 2026)
This research examines the influence of discipline and allowances on organizational performance and job satisfaction within human resource management practices at four-star hotels in Surabaya. Concurrent with the increasing competition in the hospitality industry, hotels increasingly require an effective HR management system to maintain service consistency and operational stability. Discipline and allowances are assessed as crucial HR mechanisms that play a vital role in shaping employees’ work attitudes and supporting the achievement of organizational performance in a service-based work environment. A quantitative approach was employed through the distribution of structured questionnaires to a total of 285 respondents selected using the purposive sampling technique. Data analysis was conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The research findings indicate that discipline has a positive and significant effect on organizational performance and job satisfaction. Allowances also have a positive and significant effect on organizational performance and job satisfaction. These findings affirm the importance of structured HR practices, particularly clear discipline standards and a transparent allowances system, for building positive work perceptions and maintaining organizational effectiveness. This study provides relevant managerial implications and contributes to the development of HR studies within the hospitality industry.